A Study on Water Resources Carrying Capacity Based on Water Usage Intensity in Hainan Province. Issue 3 (February 2019) - Deng, Wei; Yan, Long; Wang, Yong; Jin, Xiaohui; Hu, Yajie
Abstract: Since the establishment of Hainan Province 30 years ago, the population and the ecocomy have been developed rapidly. At the same time, the contradiction between water resources and the economic and social development has also gradually emerged. How to realize the balance of the two is one of the problems that need to be solved urgently. To find out the carrying capacity of water resources to the social economy is a prerequisite for solving this problem. Based on the current water usage intensity, this paper makes a preliminary calculation of the carrying capacity of water resources in Hainan Province, and analyzes the current carrying capacity of Hainan Province. The results show that, under the existing development status and multi-year average condition, 75% assurance rate and 90% assurance rate, the population that can be carried is 24.0464 million, 17.1512 million and 12.773 million, respectively. In general, the carrying capacity of water resources is relatively strong. Regionally speaking, under the condition of multi-year average condition and 75% assurance rate, there is no overloaded county or city, and some of the counties and cities under the condition of 90% assurance rate are in overloaded condition, which are Haikou, Lingao, Dongfang and Sanya, and Danzhou is in the critical overload state. Cities and counties under the overload or critical overload state are mainly distributed in the western coastal region, and cities and counties under the surplus state are mainly distributed in the central mountainous areas and the eastern coastal areas.